2005
DOI: 10.2527/2005.832376x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of microbial phytase addition with or without the trace mineral premix in nursery, growing, and finishing pig diets1,2

Abstract: Two experiments were conducted to determine the interactive effects of phytase with and without a trace mineral premix (TMP) in diets for nursery, growing, and finishing pigs on growth performance, bone responses, and tissue mineral concentrations. Pigs (initial and final BW of 5.5 and 111.6 kg [Exp. 1] or 5.4 and 22.6 kg [Exp. 2]) were allotted to treatments on the basis of BW with eight (Exp. 1) or six (Exp. 2) replications of six or seven pigs per replicate pen. Pigs were started on the diets the day of wea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
2
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 9 publications
0
6
2
1
Order By: Relevance
“…Only one study demonstrated a positive effect of phytase on Mn absorption, which was indicated by increased bone Mn concentration [22]. Results of the current study indicate that Mn status in pigs (indicated by Mn content of bone and kidney) only improved by inclusion of 20,000 FTU/kg, but not by 500 or 1,000 FTU of phytase per kg.…”
Section: Discussioncontrasting
confidence: 47%
See 2 more Smart Citations
“…Only one study demonstrated a positive effect of phytase on Mn absorption, which was indicated by increased bone Mn concentration [22]. Results of the current study indicate that Mn status in pigs (indicated by Mn content of bone and kidney) only improved by inclusion of 20,000 FTU/kg, but not by 500 or 1,000 FTU of phytase per kg.…”
Section: Discussioncontrasting
confidence: 47%
“…Greater improvement in Zn availability by the addition of microbial phytase in pig diets was reported by several authors [3,22,23]. The improved availability generated by phytase is assumed to reduce the need for Zn supplementation in diets fed to pigs [24,25] and it may be possible to remove the micro mineral premix in diets fed to finisher pigs [22,23]. A metaanalysis indicated that phytase inclusion up to 500 FTU/kg rapidly increased the generated digestible Zn, after which there is a much slower increase in digestible Zn [4].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Therefore, we would not expect an increase in the percentage absorption of these trace elements by the addition of E. coli phytase because our test diets were not deficient in these nutrients. However, when corn-SBM test diets were deficient in 1 or more trace elements, A. niger phytase was effective in increasing trace element use by swine (Adeola, 1995;Stahl et al, 1999;Shelton et al, 2005).…”
Section: Discussionmentioning
confidence: 94%
“…A deficiência de zinco pode resultar em anormalidade fetal ou do crescimento esquelético, retardo do crescimento, ou dermatite (BAKER; AMMERMAN, 1995;SHELTON et al, 2005). Payne, et al (2006) O mecanismo que estaria relacionado ao controle de diarreia, ainda não está bem esclarecido.…”
Section: Conteúdo Mineral E Densidade óSseaunclassified